2016
DOI: 10.1130/g38147.1
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of the Wyoming craton: Seismic evidence and geodynamic processes

Abstract: Cratons are old and strong continental cores where the lithosphere is thick and remains largely undeformed for 2–3 b.y. Unlike typical cratons, the Wyoming craton underwent pervasive deformation ca. 80–55 Ma during the Laramide orogeny in the west-central United States, and has been subsequently encroached upon by the Yellowstone hotspot since 2.0 Ma. However, the mechanism for the deformation and the craton-hotspot interaction are not well understood. We present here a three-dimensional shear wave velocity mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 31 publications
5
42
0
Order By: Relevance
“…Similar to the cratonic blocks beneath Congo, the Tanzania lithosphere has notably high Vs . The asymmetry of the Tanzania Craton agrees with prior work proposing that the craton may be thermally eroded along the Eastern Branch (e.g., Ebinger et al, ; Weeraratne et al, ); thermal erosion has also been suggested for other cratonic regions, including the North China and Wyoming Cratons (e.g., Dave & Li, ; Gao et al, ; Lee et al, ; Xu, ; Zhang et al, ). Geodynamic models suggest that prior cratonic root metasomatism enables thermal erosion to take place (e.g., Snyder et al, ; van Wijk et al, ; Wang et al, ), and we note that this region coincides with earlier Pan‐African collision and prior alteration (Collins & Piesarevsky, ; Koornneef et al, ; Porada, ; Rino et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the cratonic blocks beneath Congo, the Tanzania lithosphere has notably high Vs . The asymmetry of the Tanzania Craton agrees with prior work proposing that the craton may be thermally eroded along the Eastern Branch (e.g., Ebinger et al, ; Weeraratne et al, ); thermal erosion has also been suggested for other cratonic regions, including the North China and Wyoming Cratons (e.g., Dave & Li, ; Gao et al, ; Lee et al, ; Xu, ; Zhang et al, ). Geodynamic models suggest that prior cratonic root metasomatism enables thermal erosion to take place (e.g., Snyder et al, ; van Wijk et al, ; Wang et al, ), and we note that this region coincides with earlier Pan‐African collision and prior alteration (Collins & Piesarevsky, ; Koornneef et al, ; Porada, ; Rino et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Proposed explanations for the volcanic perimeter and stable, uplifted interior include lithosphere delamination along the plateau's margins (Levander et al, 2011), lithospheric thinning through transient heating and/or melt-induced erosion Roy et al, 2009;van Wijk et al, 2010;Wannamaker et al, 2008), and hydration of the lower crust (Jones et al, 2015). At the Wyoming craton, the Archean lithosphere may have been modified and eroded by processes related to both the Laramide orogeny (e.g., Humphreys et al, 2015) and, more recently, the Yellowstone hotspot (e.g., Dave & Li, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Archean cratons are usually underlain by thick (>200 km), cold, chemically refractory, and high‐velocity subcontinental lithospheric mantle (SCLM), which prevents cratonic lithosphere from being recycled by mantle convection for billions of years (Griffin et al, ; Lee et al, ; Yuan & Romanowicz, ). However, the reactivation of Archean cratons, which could result in the removal of a large part of SCLM, has been suggested to take place in many Archean cratons (Chen, ; Dave & Li, ; Gao et al, ; Guo, Afonso, et al, ; Lei, ; Zhao et al, ; Zheng et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Archean cratons are usually underlain by thick (>200 km), cold, chemically refractory, and high-velocity subcontinental lithospheric mantle (SCLM), which prevents cratonic lithosphere from being recycled by mantle convection for billions of years Lee et al, 2001;Yuan & Romanowicz, 2010). However, the reactivation of Archean cratons, which could result in the removal of a large part of SCLM, has been suggested to take place in many Archean cratons (Chen, 2010;Dave & Li, 2016;Gao et al, 2004;Lei, 2012;Zhao et al, 2009;Zheng et al, 2007;Zhu et al, 2011). observations suggest that lithospheric rejuvenation also occurs at the margins of Ordos during the late Cenozoic, resulting in significant intracratonic heterogeneities (Dong et al, 2014;Yu & Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%